2021
DOI: 10.3389/fmicb.2021.746550
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Tumor Domain-Containing Proteases-Deubiquitylation Enzyme Gene SsCI33130 Involved in the Regulation of Mating/Filamentation and Pathogenicity in Sporisorium scitamineum

Abstract: Sugarcane is an important sugar crop. Sugarcane smut, caused by Sporisorium scitamineum, is a worldwide sugarcane disease with serious economic losses and lack of effective control measures. Revealing the molecular pathogenesis of S. scitamineum is very helpful to the development of effective prevention and control technology. Deubiquitinase removes ubiquitin molecules from their binding substrates and participates in a variety of physiological activities in eukaryotes. Based on the transcriptome sequencing da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
(57 reference statements)
2
6
0
Order By: Relevance
“…In this study, the expression of the SsCI80130 gene in the knockout mutants was not detected during the haploid sporidia culture, sexual mating culture, or sugarcane bud infection, while the expression level of the gene in the complementary mutants returned to that of the wild type. These results showed that the quality of knockout mutants and complementary mutants constructed in this study was reliable (the SsCI80130 gene was completely deleted in the knockout mutants and almost completely restored in the complementary mutants), which was similar to a previous study on S. scitamineum by Li et al [ 16 , 37 ]. The obtained high-quality knockout mutants and complementary mutants laid the foundation for further gene function research.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, the expression of the SsCI80130 gene in the knockout mutants was not detected during the haploid sporidia culture, sexual mating culture, or sugarcane bud infection, while the expression level of the gene in the complementary mutants returned to that of the wild type. These results showed that the quality of knockout mutants and complementary mutants constructed in this study was reliable (the SsCI80130 gene was completely deleted in the knockout mutants and almost completely restored in the complementary mutants), which was similar to a previous study on S. scitamineum by Li et al [ 16 , 37 ]. The obtained high-quality knockout mutants and complementary mutants laid the foundation for further gene function research.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, there was no obvious difference in the morphology of the recovered hyphae and the hyphae produced under the normal condition. The results showed that the SsCI80130 gene may regulate the sexual mating and pathogenicity of S. scitamineum by regulating the cAMP signaling pathway and synthesis of the tryptophol, which is similar to the findings of Li et al [ 37 ]. Moreover, in the abiotic-stress experiment with the addition of CR, SDS, or H 2 O 2 , the growth rate of the knockout mutants was significantly inhibited compared to the wild type and complementary mutants, indicating that the SsCI80130 gene also plays an important role in maintaining the cell-wall integrity and oxidative-stress tolerance of S. scitamineum .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The Δ MoUBP8 mutant is slightly reduced in both mycelial growth and melanin synthesis [ 52 ]. In S. scitamineum , the DUB gene SsCI33130 is not relevant to growth [ 57 ].…”
Section: Biological Functions Of Dubs In Different Pathogenic Fungimentioning
confidence: 99%
“…For the plant pathogenic fungus S. scitamineum , sexual mating is closely related to its pathogenicity. The OTU1 deubiquitinase gene SsCI33130 regulates the expression of genes involved in the synthesis of cAMP and tryptophol [ 57 ]. The cAMP and tryptophol are small molecule signaling substances required for the sexual mating of S. scitamineum .…”
Section: Biological Functions Of Dubs In Different Pathogenic Fungimentioning
confidence: 99%